Assessment of Functional Properties of Cartilage using Double Quantum Filtered MRI. Issue 1622 (2014) - Benjamini, Dan; Eliav, Uzi; Nevo, Uri; Basser, Peter J.; Horkay, Ferenc
ABSTRACT: It is biologically and clinically important to understand and explain the functional properties of cartilage, such as its load bearing and lubricating ability, in terms of the structure, organization, components and their interactions. Our approach tries to explain functional material properties of these tissues as arising from polymeric interactions between and among the different molecular constituents within the tissues at different hierarchical lengthscales. We treat the tissue effectively as a complex molecular composite containing highly charged polysaccharide microgels trapped within a fine collagen meshwork. We have been developing a multi-scale experimental and theoretical framework to explain key material properties of cartilage by studying those of its constituents and the interactions among them at a variety of length and time scales. We use this approach to address important biological questions. One novel application we highlight here is the use of non-invasive magnetic resonance imaging (MRI) methods to characterize different components and compartments within cartilage and the different water environments associated with each one, in an attempt to provide a comprehensive picture of the mechanical/chemical state of cartilage.